The Compliance of Chronic Kidney Failure Patients Underwent Hemodialysis at Gunung Jati Regional Hospital, Cirebon City - Kusdiani, Yulia Sopi; Yasin, Nanang Munif; Wahyuningrum, Retno (Journal of Health Economic and Policy Research (JHEPR), 2025)
Background: Non-compliance in patients with hemodialysis has a tremendous negative impact. Complications of the disease result in a poor quality of life. This study aimed to determine the compliance and characteristics of patients with chronic kidney failure undergoing hemodialysis at Gunung Jati Regional Hospital, Cirebon City. Methods: This study employed a non-experimental design, with data collected prospectively using a questionnaire. The subjects of this study were chronic renal failure patients who underwent hemodialysis therapy at the Hemodialysis Unit of Gunung Jati Regional Hospital in Cirebon City and were treated at the clinic from January to March 2020. Non-random sampling was used in this study because the sample size was not calculated. The total number of patients undergoing hemodialysis was 133, of whom 44 met the study criteria, with a total of 95 cases. The study tool assessed patients' compliance with chronic kidney failure undergoing hemodialysis, specifically the End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ). Results: The 44 research subjects were patients with chronic kidney failure who underwent hemodialysis therapy at the hemodialysis unit of Gunung Jati Regional Hospital in Cirebon City, and were treated at the clinic from January to March 2020. The data collection method involved filling out a questionnaire through interviews. Data were analyzed using qualitative descriptive analysis. The results showed that all patients with chronic renal failure who underwent hemodialysis at the hemodialysis unit at Gunung Jati Regional Hospital in Cirebon City have good adherence (100%) to therapy. Conclusion: All patients in this study sample were reported to be compliant with hemodialysis therapy, with major cost consumption of Chronic Kidney Disease (CKD) patients at mental health clinics, and the lowest was for patients seeking treatment at the lung clinic. Keywords: Chronic Kidney Failure, Compliance, Hemodialysis.